Feminist and gender perspectives in Costa Rican foreign policy: initial analytical notes - Artavia Medrano, Argentina (2023)
This article describes the government proposal "Equality Policy in Costa Rica's Foreign Action" (2022). The contextual analysis was carried out considering the institutional and political framework in which Costa Rican foreign policy is being developed, as well as the long historical tradition of the country in promoting and defending human rights, mainly women's. The fact that it was the first policy with a "feminist" perspective was also considered relevant. For this research, a review of relevant specialized literature and documents was carried out, as well as semi-structured interviews with female officials with expertise on the subject. The research, was exploratory and descriptive in nature and used a theoretical and conceptual framework based on feminist and gender approaches in foreign policy, with the purpose of identifying whether feminist and gender perspective has been incorporated in practices and concepts used in Costa Rican foreign action, specifically the design of the aforementioned policy. Preliminarily, this article concludes that there are sustained efforts and important advances to incorporate gender perspective in decision-making and in the construction of spaces that guarantee gender equality, as well as to ensure the coherence of external action. The purpose of this article is to provide elements for further reflexion and research on the analysis of foreign policy and the design and formulation of gender equality policies within the Ministry of Foreign Affairs of Costa Rica.